SISTEM INFORMASI PAKAIAN JADI BERBASIS WEB (STUDI KASUS WOOD PECKER STORE) - Widia Arfianto; Hendro Joko Prasetyo; Fajar Budi Hartono; Nurhasan Nugroho (LPPM Universitas Widya Dharma, 2021)
Wood Pocker Store is a distro that still uses word of mouth marketing model. as a consequence, the development of Wood Pecker Store’s marketing has been slow and pre-determined sales targets not yet reached. Website-based apparel information systems are one way of marketing model that is more effective than word of mouth. The website can reach a wider range of customers moreover the system can also serve orders for Wood Pocker Store products. This study aims to build a web-based apparel system. This system is expected to make Wood Pocker Store to expand the marketing reach of their products. In addition, this website is expected to make Wood Pocker Store customers to choose and order Wood Pocker Store products more easier that before and they can do it without come to the store directly. This system also supports the government's program to stay at home due to the Covid pandemic. The stages that will be carried out in this research are data requirenment, design and implementation. Data requirenment was carried out by interview and observation. Context diagrams, DFD, ERD, and interface design are the results of the design stage. At the implementation stage, all of these designs are implemented into a usable system. The result of this research is a system that can be used as a media for promotion or ordering from the Wood Pocker Store.